METHODS PIPELINE REHABILITATION OF WATER SUPPLY - , Н. Ю., Н. М., В. М. (Municipal economy of cities (Technical science), 2013)
Examines the current methods of pipeline rehabilitation of water supply systems, analyzes their advantages and disadvantages. Offers the most advanced methods of rehabilitation.